New in recommendations on primary percutaneous coronary intervention for myocardial infarction with ST segment elevation - M.Т. Vatutin; Y.V. Yeshchenko; K.S. Gasendich (Кардіохірургія та інтервенційна кардіологія)
The review presents updated recommendations of American College of Cardiology, American Heart Association and the Society for Cardiovascular Angiography and Interventions regarding multivessel percutaneous coronary intervention, as well as aspiration thrombectomy in patients with ST-elevation myocardial infarction undergoing primary percutaneous coronary intervention.